2013
DOI: 10.1111/jgs.12171
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Barriers to Antihypertensive Medication Adherence: Findings from the Cohort Study of Medication Adherence Among Older Adults

Abstract: Objectives We assessed whether socio-demographic, clinical, health care system, psychosocial, and behavioral factors are differentially associated with low antihypertensive medication adherence scores among older men and women. Design / Setting A cross-sectional analysis using baseline data from the Cohort Study of Medication Adherence in Older Adults (CoSMO, n=2,194). Measurements Low antihypertensive medication adherence was defined as a score <6 on the 8-item Morisky Medication Adherence Scale. Risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
5
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 43 publications
5
85
5
5
Order By: Relevance
“…We found that male patients were more non-adherent to medication as compared with females and this finding is in agreement with other studies (25,27). In contrast, Holt et al showed no differences between the sexes regarding adherence to medication (28) and Shan et al found that females were more non-adherent to medication than males (29).…”
Section: Discussionmentioning
confidence: 86%
“…We found that male patients were more non-adherent to medication as compared with females and this finding is in agreement with other studies (25,27). In contrast, Holt et al showed no differences between the sexes regarding adherence to medication (28) and Shan et al found that females were more non-adherent to medication than males (29).…”
Section: Discussionmentioning
confidence: 86%
“…Antihypertensive adherence might be a particular concern for older adults who have multiple chronic conditions 4, 5, 6, 8, 20. Many studies have examined major barriers and predictors of nonadherence among hypertensive patients,5, 7, 9, 11, 44, 45 and some focused on older adults 6, 46. Potential barriers to adherence among older adults can be classified into 3 categories: (1) patient‐related factors, including sociodemographics, psychosocial factors, comorbidities, cognitive ability, and health beliefs; (2) medication‐related factors, including the number of medications taken, adverse side effects, and complex medication regimens; and (3) other factors, including the patient‐prescriber relationship, access to medication and cost, and social support 6, 46.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional analysis of data from the Cohort Study of Medication Adherence among Older Adults (CoSMO) ( N = 2,194), the overall prevalence of low medication adherence did not differ according to sex ( P = 0.21) [ 19 ]. However, women who were nonadherent were more likely to report dissatisfaction with communication with their health care provider (OR = 1.75 women, 1.16 men; P = 0.13) and depressive symptoms (OR = 2.29 women, 0.93 men; P = 0.11).…”
Section: Socioeconomic and Sociodemographic Factorsmentioning
confidence: 91%